Screening backcross derived population of groundnut (Arachis hypogaea L.) for resistance to rust and late leaf spot diseases: SCREENING BACKCROSS POPULATION OF GROUNDNUT FOR RUST AND LATE LEAF SPOT DISEASES - P RAMAKRISHNAN; N MANIVANNAN; A MOTHILAL; L MAHALINGAM (Journal of Oilseeds Research, 2019)
A set of 88 groundnut backcross derived progenies in BC1F2 generation of the cross CO 7 × GPBD 4 were evaluated during kharif 2016 against rust and late leaf spot. Field evaluation identified 19 progenies with rust and late leafspot resistance. These backcrossed progenies may be subjected to yield assessment for further release as an improved variety